Bilingual health care in Quebec: Public policy, vitality, and acculturation issues - Bourhis, Richard Y. (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Abstract The first part of this chapter offers the Interactive Acculturation Model (IAM), which provides an intergroup approach to minority/majority group relations in multilingual settings. The ethnolinguistic vitality framework is the first element of the IAM as it describes the relative strength and weaknesses of linguistic communities in contact. Four language policies regulating the status of linguistic communities constitute the key second element of the IAM. Third, the acculturation orientations of minority and majority group speakers are described as they interact to yield harmonious, problematic or conflictual intergroup relations. As an application of the IAM, the second part of the chapter analyzes bilingual health care policies for official language minorities in Canada and Quebec. A detailed analysis of bilingual health care institutions serving the English-speaking communities of Quebec closes with a case study of a recent Quebec Government health care law that threatened to undermine the institutional vitality of the Anglophone minority of Quebec. Key words: Interactive Acculturation Model (IAM), English-speaking communities of Quebec, health care policies.
Chapter 14

Health care professionals and official-language minorities in Canada, 2001 and 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistics Canada, 2017)

Professionnels de la santé et minorités de langue officielle au Canada, 2001 et 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistique Canada, 2017)

Active offer, actors, and the health and social service system: An analytical framework - Vézina, Sylvain; Savard, Sébastien (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre active, acteurs et système de santé et de services sociaux : un cadre d’analyse - Vézina, Sylvain; Savard, Sébastien (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Ce chapitre présente un cadre théorique inspiré de l’analyse stratégique aussi nommée sociologie des organisations. Par cette approche, le chercheur tente de découvrir les objectifs et stratégies des acteurs en présence pour mieux saisir la dynamique du système d’action tout en prenant en compte les contraintes issues de la structure formelle. On y traite des concepts de système d’action, de pouvoir, de règle du jeu, de changement, de stratégie, d’acteur, d’enjeu, d’organisation et d’environnement, lesquels rendent compte de la complexité des défis entourant la pratique de l’offre active en santé et services sociaux. Une des contributions majeures de cette approche est qu’elle fournit un cadre d’analyse permettant de mieux saisir la relation entre l’acteur et le système, deux composantes essentielles tant à la compréhension de notre objet qu’à l’identification de stratégies d’action par les acteurs du milieu. Mots-clés : offre active, services sociaux et de santé, système d’action, pouvoir, zone d’incertitude, analyse stratégique, sociologie des organisations, changement, stratégie, acteur, enjeu, organisation, environnement.
Chapitre 1